1996
DOI: 10.1159/000147812
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopy of the Basal Surface of the Epidermis of Human Digits

Abstract: The epidermal-dermal junction of the volar skin of human digits was examined by scanning electron microscopy (SEM). Fixed specimens obtained from cadavers were treated with 6 N NaOH to exfoliate the epithelium. The three-dimensional features of the basal surfaces were clearly visualized by SEM. Epithelial prolongations (intermediate and limiting ridges) protruded towards the dermis, and transverse ridges were visible between them. Nerve fibers and Schwann cells were aggregated around the sweat ducts on the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…The finding that smaller fingers have better acuity suggests an inverse relationship between finger size and the density of Merkel cells, the putative mechanotransducers for statically impressed stimuli (Iggo and Muir, 1969;Ogawa, 1996;Johnson, 2001). Given that Merkel cells cluster around the bases of sweat pores in the deep epidermis (Yamada et al, 1996), we reasoned that sweat pore density would provide a measurable correlate of Merkel cluster density. High-resolution scans revealed that sweat pore density is indeed greater in smaller fingers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The finding that smaller fingers have better acuity suggests an inverse relationship between finger size and the density of Merkel cells, the putative mechanotransducers for statically impressed stimuli (Iggo and Muir, 1969;Ogawa, 1996;Johnson, 2001). Given that Merkel cells cluster around the bases of sweat pores in the deep epidermis (Yamada et al, 1996), we reasoned that sweat pore density would provide a measurable correlate of Merkel cluster density. High-resolution scans revealed that sweat pore density is indeed greater in smaller fingers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to sensory nerves, autonomic nerves never innervate the epidermis in mammals. Sensory nerves innervate the epidermis and dermis as well as the subcutaneous fatty tissue as a three-dimensional network (425,881,951). Most of the nerve fibers are found in the mid-dermis and the papillary dermis.…”
Section: A Neuroanatomy and Neurophysiology Of Cutaneous Nervesmentioning
confidence: 99%
“…Training reportedly improves the tactile discrimination of frequency (Harris et al, 2001;Imai et al, 2003), dot location (Sathian and Zangaladze, 1998;Grant et al, 2000;Kauffman et al, 2002), roughness (Sathian and Zangaladze, 1997;Harris et al, 2001), punctate pressure (Harris et al, 2001), and electrotactile patterns (Weiss et al, 2007). In contrast, several studies have reported that GOT performance improves little, if at all, with repeated testing (Van Boven and Johnson, 1994;Goldreich and Kanics, 2003;Wong et al, 2011b; but see Sathian and Zangaladze, 1997).…”
Section: Tactile Perception Improves With Trainingmentioning
confidence: 99%